Growth Inhibitory Effects of Red and Yellow Passion Fruits against MRSA and ESBL-producing Bacteria - Aprelita Nurelli Dwiana; Achmad Toto Poernomo; Iif Hanifa Nurrosyidah; Isnaeni; Dian Rahmawaty; Idha Kusumawati (Universitas Airlangga, 2023)
Background: Red passion fruit (Passiflora edulis Sims) and yellow passion fruit (Passiflora edulis f. flavicarpa) are native Indonesian fruits with numerous health benefits. This study used de Man, Rogosa, and Sharpe (MRS) medium for fermentation. Probiotics are beneficial microorganisms obtained from fermented food or drink (Hamid et al., 2020). Probiotics and lactic acid bacteria, which are known to have various benefits, particularly as antibacterial, are among the active components identified in passion fruit pulp. Objective: This study examinedthe antibacterial activity of red and yellow passion fruits. Methods: Freshly collected passion fruit pulps were fermented in MRS medium in a shaker incubator for 48 hours at 24°C. The filtrates from the fermented broth were tested against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) and extended-spectrum beta-lactamase (ESBL)-producing bacteria. The analyses applied the streak plate method and the total plate count method. Results: The Minimum Inhibitory Concentrations (MICs) of red passion fruit ferment filtrate against MRSA 10 and MRSA 11 were 50% and 60%, respectively, and of yellow passion fruit ferment filtrate against MRSA 10 and MRSA 11 were both 30%. Meanwhile, the MICs of red passion fruit ferment filtrates were 35% against ESBL 41 and ESBL 43 and 25% against ESBL 45 and ESBL 47, whereas the MICs of yellow passion fruit (Passiflora edulis f. favicarpa) ferment filtrates were 25% against ESBL 41 and ESBL 43, and 12.5% against ESBL 45 and ESBL 47. Red passion fruit (Passiflora edulis Sims) and yellow passion fruit (Passiflora edulis f. flavicarpa) ferment filtrates became growth inhibitors against the clinical isolates of MRSA and ESBL-producing bacteria with an optimal fermentation time of 24 hours and an optimal concentration of 75%. Conclusion: The results of this study found that the fermented filtrates of red and yellow passion fruits in MRS media could be developed as an antibacterial against MRSA and ESBL-producing bacteria.